Are There Any Differences in Personality Traits and Life Satisfaction Between Future Preschool and Primary School Teachers?. Issue 3 (2nd July 2016) - Vorkapić, Sanja Tatalović; Čepić, Renata; Šekulja, Ivana
ABSTRACT: The main aim of this study was to examine personality traits and life satisfaction of future preschool and primary school teachers and to examine if there are differences between these two groups of students. The study was conducted on a sample of 290 students of the University of Rijeka attending Early and Preschool Education and Teacher Education programs. Significantly higher levels of life satisfaction and personality traits were found: extraversion, conscientiousness, agreeableness, and openness to experience. Neuroticism was significantly decreased in both groups of participants. Differences in these two groups of students are not significant in life satisfaction and personality traits except in conscientiousness, which is significantly higher among future primary school teachers as opposed to future preschool teachers. Given the significant correlation of age and the year of study with personality traits, the established findings are discussed in terms of the varying length of the study programs.